Optimization of the performance of a double-chamber microbial fuel cell through factorial design of experiments and response surface methodology. (15th June 2015) - Madani, Sara; Gheshlaghi, Reza; Mahdavi, Mahmood Akhavan; Sobhani, Mahdieh; Elkamel, Ali
Highlights: Design of experiment was used to optimize performance of MFCs. The optimal levels of pH and buffer concentration of catholyte were assessed. The joint effect between the factors was highly significant in the responses. Buffer concentration affected the responses differently at different pH levels. Lower optimum level of buffer concentration made the process more economic. Abstract: Although microbial fuel cells are potential candidates for electricity generation with concomitant treatment of wastewater, operational and technological improvements are still required to make them a cost effective process. In this paper, a full factorial design in combination with a central composite design were employed to probe the effects of pH and buffer concentration of catholyte on the performance of a two chamber microbial fuel cell. It was observed that at high level of buffer concentration (150 mM) varying the pH between 5.8 and 7.4 did not markedly influence the maximum power density and columbic efficiency. However, at a low level of buffer concentration (25 mM) reducing the pH led to higher power density. Furthermore, it was observed that higher concentrations of buffer were beneficial to power generation when pH was at its high level, but negatively impacted the cell performance at low pH levels. The highest maximum power was predicted to be 461 mW m −2 (at a pH of 6.3 and a buffer concentration of 82 mM) and this was confirmed by experimental results. The findings of this paper highlight the importance of the joint effect of pH and buffer concentration, which is even more influential than their main individual effects.